Sustainable soil and crop management of cassava in Asia: a reference manual - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2014)
This book is another collaborative effort between CIAT and The Nippon Foundation to review and summarize the results of many years of research on cassava, especially that conducted in Asia by CIAT in collaboration with national programs in the various cassava-growing countries. [...] The main objective was not only to continue the development of new technological options to improve cassava yield while protecting the soil from degradation but also to enhance the adoption of these technologies by cassava farmers.